ANALISIS KEPUASAN ANGGOTA TERHADAP LAYANAN PEMBIAYAAN DI KSPPS ”USAHA BAROKAH” JATIPURNO (Studi Kasus Syariah KSPPS Usaha Barokah Jatipurno): Studi Kasus Syariah KSPPS Usaha Barokah Jatipurno - Yusuf Sabila Rosyada; Abdul Haris Romdhoni; Rukmini (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the level of member satisfaction with financing services at KSPPS Usaha Barokah Jatipurno. The research method used is descriptive quantitative with the Customer Satisfaction Index (CSI) approach. Data were obtained by distributing questionnaires to cooperative members who had received financing services. The five main aspects measured include product quality, service quality, emotional factors, financing price/margin, and ease of access. The results showed that the CSI value reached 83.4% which is included in the very satisfied category. This indicates that the financing services provided by KSPPS Usaha Barokah Jatipurno have optimally met the expectations of its members. This study contributes to the development of literature on member satisfaction in the context of Islamic financial institutions and can be a reference in evaluating the quality of cooperative services.